2022
DOI: 10.1038/s41598-022-09108-w
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions and rumen metabolite concentrations in cattle fed two different silages

Abstract: In this study, 18 animals were fed two forage-based diets: red clover (RC) and grass silage (GS), in a crossover-design experiment in which methane (CH4) emissions were recorded in respiration chambers. Rumen samples obtained through naso-gastric sampling tubes were analysed by NMR. Methane yield (g/kg DM) was significantly lower from animals fed RC (17.8 ± 3.17) compared to GS (21.2 ± 4.61) p = 0.008. In total 42 metabolites were identified, 6 showing significant differences between diets (acetate, propionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Dewhurst et al (2003), however, observed no significant differences in milk yield for cows offered ryegrass silage, or silage from ryegrass with white or red clover (Trifolium pratense) (50:50). Bica et al (2022) compared rumen metabolite concentration and CH 4 emissions from beef cattle offered red clover silage or ryegrass silage, but not a mixed sward observed no significant differences for CH 4 emissions. Wang et al (2020) conducted an in vitro experiment comparing different ryegrass cultivars and concluded that AberMagic resulted in a slightly lower CH 4 yield.…”
Section: Discussionmentioning
confidence: 93%
“…Dewhurst et al (2003), however, observed no significant differences in milk yield for cows offered ryegrass silage, or silage from ryegrass with white or red clover (Trifolium pratense) (50:50). Bica et al (2022) compared rumen metabolite concentration and CH 4 emissions from beef cattle offered red clover silage or ryegrass silage, but not a mixed sward observed no significant differences for CH 4 emissions. Wang et al (2020) conducted an in vitro experiment comparing different ryegrass cultivars and concluded that AberMagic resulted in a slightly lower CH 4 yield.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study showed that a greater NDFom concentration resulted in lower CH 4 production 13 , which might explain why CH 4 production was lower in T than RG in the present experiment. It has been shown that diets with red clover reduced in vivo CH 4 production compared to diets with grass in cattle (17.8 vs 21.2 g/kg DM intake, respectively) 52 . However, in the present study, we did not observe lower CH 4 production in T + RC compared to T. This supports earlier findings showing no such effect in diets with 60/40 perennial ryegrass and clover 20 .…”
Section: Discussionmentioning
confidence: 99%